PENERIMAAN DIRI PADA INDIVIDU YANG MEMILIH UNTUK TIDAK MENIKAH - Salim, Gunawan; Purnomodi, Faqih; Anniez Rachmawati Musslifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Marriage is still viewed as the main norm of adult life in Indonesian culture, so individuals who choose not to marry often face social pressure and negative stigma. This condition requires self-acceptance skills so that individuals can maintain their psychological well-being. This study aims to understand the process of self-acceptance in individuals who choose not to marry in the Indonesian context. The study uses a qualitative approach with a phenomenological design. The participants consisted of five adult women, ranging from early adulthood to late adulthood, who consciously chose not to marry. Data were collected through semi-structured in-depth interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The results showed that self-acceptance was formed through a process of continuous self-reflection, influenced by life experiences and social interactions. Self-acceptance is reflected in unconditional acceptance, a realistic view of oneself, self-esteem that does not depend on marital status, authenticity, and openness to emotional experiences. Self-acceptance acts as a protective mechanism that maintains psychological well-being.